Selective harmonic elimination (SHE) based 3-phase multilevel voltage source inverter (VSI) for standalone applications - Shanono, Ibrahim Haruna; Nor Rul Hasma, Abdullah; Hamdan, Daniyal; Aisha, Muhammad (Springer Nature, 2019)
The breakthroughs in power electronics semiconductor technology have led to the raised in popularity of Multi-level Voltage Source Inverters, which is the reason industries and researchers are relentlessly working towards extending it to both medium and high-power applications. Consequently, this paper presents a modified Selective Harmonic Elimination Pulse Width Modulation (SHE-PWM) controlled three-phase 5-level Multi-level Inverter (MLI) topology. The work is an extension of a single-phase topology proposed by the authors. The uniqueness of the proposed topology is that it comprises of six Cascaded H-bridge modules (two modules per phase) that are powered through a single direct current (DC) source, hence eliminating the need for multiple DC sources. In addition, conventional 5-level MLI has two switching angles (n = 2), which restricts its harmonic elimination capability to one (n = 1) lower order harmonics. This study removes that restriction by utilising the concept of multiple switching per step, resulting in the superimposing of 12 notches (n = 12) on the output voltage at the 3/9 distribution ratio. With the fundamental switching SHE-PWM, twelve non-linear, transcendental equations are generated, and they are optimally solved using the Hybrid Coded Genetic Algorithm to eliminate 11 (n − 1) lower-order harmonics. The low-switching frequency results in less electromagnetic interference as well as reduced switching loss, which improves the overall inverter efficiency. The topology has less output Total Harmonics Distortion, fewer components, and lower weight and cost than conventional topologies. The circuit was designed and validated through simulations performed in PSIM software.